Psikoterapi Islam dalam Menangani Pasien Skizofrenia di Yayasan Sinar Jati Lampung - Nurpratiwi, Nurpratiwi; Aisyah, Umi; Rogamelia, Risna (Jurusan Bimbingan dan Konseling Islam, 2025)
Schizophrenia is a complex mental disorder that affects the cognitive, emotional, and behavioral aspects of sufferers. At the Sinar Jati Lampung Foundation, the majority of schizophrenia cases are caused by drug abuse. This study examines the effectiveness of Islamic psychotherapy as an alternative therapy modality in the rehabilitation of schizophrenia patients. Conventional approaches that rely on medical-pharmacological interventions often fail to adequately address the psychosocial aspects of patients. Islamic psychotherapy offers a holistic approach that integrates the spiritual dimension to achieve psychological balance and improve quality of life. The research method uses a descriptive qualitative approach with a field research design. The research subjects consisted of 7 informants: 1 counselor, 1 social worker, 1 spiritual guide, and 4 schizophrenia patients. The results of the study identified the application of Islamic psychotherapy through four stages: preparation and planning, orientation and socialization, implementation including ritual worship, dhikr, and religious studies, and evaluation of therapy progress. Islamic psychotherapy has a positive impact on the psychological and spiritual stability of patients, contributing significantly to the recovery of schizophrenia.